The Rise of E-Learning in COVID-19 Pandemic in Private University: Challenges and Opportunities - Daniel Hermawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The COVID-19 pandemic which is occurring all over the world indeed has many negative impacts in various aspects. On the other hand, the COVID-19 pandemic aroused the use of e-learning which has been seen as a complementary medium in the education process in Indonesia. This research aims to explore the challenges and opportunities felt by students in private university by implementing e-learning as an innovative learning method in the future. Through the mixed method approach, it can be concluded that e-learning can be accepted as an educational solution in dealing with the COVID-19 pandemic, but it still requires improvements in terms of comfort, infrastructure, and absorption of knowledge so that e-learning does not merely move classrooms into digital classrooms, but also provides a holistic experience that makes it easier for students to learn and gain knowledge. Research provide student perspectives in undergoing e-learning which is expected to be a recommendation for universities to provide a good e-learning experience. In addition, there is an evaluative step for the lecturer in optimally optimizing e-learning design.